Meta-Analysis: Effectiveness of SSRIs vs SSRIs in conjunction with CBT in treating depression in young adolescents - Kresnia, Gabriele Mustika; Hasuki, Winda; Pradana ratnasari, Nanda Rizqia (Indonesia International Institute for Life Sciences, 2020)
Objective: To compare the efficacy of SSRI medication alone and SSRI+CBT combined. Methods: NCBI Pubmed, DARE, CSDR and NGC were searched October-November 2019. The population size, as well as the base and endpoint CGAS mean and standard deviation from the three studies included, are recorded. Statistical analysis was done in RStudio with the